PENGARUH HARGA DAN KESADARAN MEREK TERHADAP MINAT MEMBELI PADA E-COMMERCE SHOPEE - Muhamad Galy Njoman Ari Pribowo; Meiffa Herfianti; Mimi Kurnia Nengsih (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study analyzes the influence of price and brand awareness on the buying interest of students of the Department of Informatics and Business of the Bangka Belitung State Manufacturing Polytechnic on the Shopee e-commerce platform. This research is motivated by the high use of e-commerce among students which is influenced by factors such as competitive prices and strong brand awareness. A quantitative approach was applied, with data collection through a questionnaire survey involving 90 respondents. Multiple linear regression is a useful method of analysis to assess the relationship between dependent variables (purchase intent) and independent variables (price and brand awareness). The research findings show that, both separately and in combination, price and brand awareness significantly and positively influence students' purchase intentions. Price has a significance value of 0.000 on its own, while brand awareness has a significance value of 0.002, both smaller than 0.05. Buying interest is significantly affected with an F value of 687.630, and a significance value of 0.000. The compatibility rate of the regression model was very high, with a determination coefficient (R²) of 94.2%, meaning 94.2% variation in students' buying interest with price variables and brand awareness.Keywords: Price, Brand Awareness, Buying Interest, E-Commerce